Recombination between linear double-stranded DNA substrates in vivo - Narayanan, Kulathuramaiyer; Sim, Edmund U. H.; Ravin, Nikolai V.; Choon, Weng Lee (Academic Press Inc., 2009)
Recombineering technology in E. coli enables targeting of linear donor DNA to circular recipient DNA using short shared homology sequences. In this work, we demonstrate that recombineering is also able to support recombination between a pair of linear DNA substrates (linear/linear recombineering) in vivo in E. coli. Linear DNA up to 100 kb is accurately modified and remains intact without undergoing rearrangements after recombination. This system will be valuable for direct in vivo manipulation of large linear DNA including the N15 and PY54 prophages and linear animal viruses, and for assembly of linear constructs as artificial chromosome vectors.